ANALISIS PENGARUH UKURAN PERUSAHAAN, LEVERAGE DAN GOOD CORPORATE GOVERNANCE TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Manufaktur yang Listing di Bursa Efek Indonesia Periode Tahun 2012-2014) - Verya, Endi; Indrawati, Novita; Hanif, Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Financial statement integrity is a communication media between management’s company with investment about company’s financial statement. That’s why for making financial statement must be real and really and honest. The informational of financial statement must be quality, honest, it means the informational offinancial statement free from fraud. Good financial statements are have the integrity of the information contained. Integrity of the financial statements is the extent to which the financial statements present financialinformation fairly, honestly and unbiased. This study aims to obtain empirical evidence about the influence of firm size, leverage and good corporate governance at integrity of the financial statements are measured by an index of conservatism. The sample was manufacturing companies listed on the Stock Exchange 2012-2014 period, which is determined by purposive sampling method. The statistical method used was logistic regression. These results indicate that firm size, independent commissioner, audit committees, managerial ownership and instutional ownership have and effect on integrity of financial statements. However, only leverage doesn’t provide to integrity of financial statements, but integrity financial reports influenced by firm size, and good corporate governance.Keyword : Financial Report Integrity, Firm Size, Leverage, Good Corporate Governance